Earth - "York, Penelope" (DK London, 2004)
This is a guide to the terrifying and beautiful world we live in. It explores phenomena from vicious volcanoes to wondrous waterfalls. The vocabulary used in the book is accessible to all children aged five and above with the meanings of subject-related words clearly explained in a glossary